MATHEMATICAL MODELING AND CURVE FITTING: ATEACHING METHOD APPLIED TO POPULATIONGROWTH (REMUNOM, 2025)
This work presents Mathematical Modeling as an alternative approach toteaching mathematical content in high school, promoting student protagonism in thelearning process. In addition to a brief historical contextualization, the study discussesstrategies for applying modeling in the classroom, based on concepts from MathematicsEducation.The literature review highlights modeling as an essential tool for connecting mathematicalconcepts to real-world phenomena. In this context, the theory of curve fitting was exploredusing the Least Squares method, addressing simple linear, polynomial, exponential, andlogistic models, with the latter being developed through the Ford-Walford method.Finally, practical activities are proposed for students to apply curve fitting in the creationof mathematical models, encouraging hypothesis formulation and interaction with realand social problems.